Cross-Presentation of Cell-Associated Antigens by Mouse Splenic Dendritic Cell Populations - Janssen, Edith M.; Thacker, Robert I. (Frontiers in Immunology, 2012)
Cross-presentation of cell-associated antigens (Ag) plays an important role in the induction of anti-tumor responses, autoimmune diseases, and transplant rejection. While several dendritic cell (DC) populations can induce pro-inflammatory CD8+T cell responses to cell-associated Ag during infection, in the absence of infection, cross-priming of naïve CD8+T cells is highly restricted. Comparison of the main splenic DC populations in mice– including the classic, cross-presenting CD8αDC and the recently-described merocytic DC (mcDC)– reveals that cross-priming DCs display a distinct phenotype in cell-associated Ag uptake, endosomal/lysosomal trafficking, lysosomal acidification, and Ag persistence compared to non-cross-priming DC populations. Although the CD8αDC and mcDC subsets utilize similar processing pathways to cross-present cell-associated Ag, cross-priming by CD8αDCs is associated with IL-12 production, while the superior priming of the mcDC is critically dependent on type I IFN production. This discussion illustrates how subtle differences in internal processing pathways and their signaling sequelae significantly affect the duration of Ag cross-presentation and cytokine production by DCs, thereby shaping the ensuing CD8+ T cell response.